The critical problem of cynical irony meaning what you say and ideologies of class and gender. Issue 3 (26th May 2016) - Bennett, Joe
ABSTRACT: Critical theorists such as Slavoj Žižek have for some years discussed the ideological significance of cynical or "blank" irony in fairly general terms. Less attention has been paid to the practical implications of such irony for critical semiotic analysis. With this in mind, this paper discusses the problems that sexist and "classist" jokes – specifically jokes about "chavs" – pose for the critical analyst. On the one hand, they seem to be saying deeply ideological things. On the other, their ironic nature means that they evade the claim that they are really saying, asserting, meaning anything. Theirs is a kind of blank irony which can be identified in all kinds of contemporary semiotic practice and is therefore an important phenomenon for critical analysts to get to grips with. The paper attempts to get to grips with it by outlining some semiotic clues to blank irony, and, more importantly, by suggesting some ways in which we might try to bring a critical perspective to bear in cases of cynical irony.